Protective effects of puerarin against tetrabromobisphenol a‐induced apoptosis and cardiac developmental toxicity in zebrafish embryo‐larvae. Issue 9 (5th March 2014) - Yang, Suwen; Wang, Shengrui; Sun, Fengchao; Zhang, Mengmeng; Wu, Fengchang; Xu, Fanfan; Ding, Zhishan
ABSTRACT Tetrabromobisphenol A (TBBPA), a brominated flame retardant, is detected commonly in aquatic environments, where it is thought to be highly toxic to the development of aquatic life. In this study, zebrafish embryos and larvae were used to investigate the protective effects of puerarin after exposure to TBBPA. Malformation, blood flow disorders, pericardial edema, and spawn coagulation rates increased, whereas survival decreased significantly after exposure to 0.5 and 1.0 mg L−1 TBBPA. The measured indices of morphological toxicity improved after treatment with puerarin. TBBPA also induced reactive oxygen species (ROS) production in a dose‐dependent manner. Acridine orange staining results revealed that TBBPA exposure caused cardiomyocyte apoptosis and induced the expression of three proapoptotic genes: P53, Bax, and Caspase9. In contrast, the expression of the antiapoptotic gene Bcl2 was down‐regulated. When genes related to cardiac development were assessed, the expression of Tbx1, Raldh2, and Bmp2b changed after exposure to the combination of TBBPA and puerarin. These results suggest that TBBPA induces cardiomyocyte apoptosis and ROS production, resulting in cardiac developmental toxicity in zebrafish embryos or larvae. Therefore, puerarin regulates the expression of cardiac developmental genes, such as Tbx1, Bmp2b, and Raldh2 by inhibiting ROS production, and subsequently modulates cardiac development after the exposure of zebrafish larvae to TBBPA. © 2014 Wiley Periodicals, Inc. Environ Toxicol 30: 1014–1023, 2015.